Submicron‐Sized In Situ Osmotic Pressure Sensors for In Vitro Applications in Biology. Issue 9 (13th January 2023) - Zhang, Wenbo; Bertinetti, Luca; Yavuzsoy, Efe Cuma; Gao, Changyou; Schneck, Emanuel; Fratzl, Peter
Abstract: Physical forces are important cues in determining the development and the normal function of biological tissues. While forces generated by molecular motors have been widely studied, forces resulting from osmotic gradients have been less considered in this context. A possible reason is the lack of direct in situ measurement methods that can be applied to cell and organ culture systems. Herein, novel kinds of resonance energy transfer (FRET)‐based liposomal sensors are developed, so that their sensing range and sensitivity can be adjusted to satisfy physiological osmotic conditions. Several types of sensors are prepared, either based on polyethylene glycol‐ (PEG)ylated liposomes with steric stabilization and stealth property or on crosslinked liposomes capable of enduring relatively harsh environments for liposomes (e.g., in the presence of biosurfactants). The sensors are demonstrated to be effective in the measurement of osmotic pressures in pre‐osteoblastic in vitro cell culture systems by means of FRET microscopy. This development paves the way toward the in situ sensing of osmotic pressures in biological culture systems. Abstract : Novel liposome‐based local sensors are developed for in situ measurements of osmotic pressures in cell cultures exploiting the resonance energy transfer (FRET) principle, which has not been achieved so far. With the help of fluorescence microscopy, the feasibility of in situ osmotic pressure imaging in pre‐osteoblastic in vitro cell culture systems is demonstrated.